The State of Democratic Theory - Shapiro, Ian (Book collections on Project MUSE., 2003)
What should we expect from democracy, and how likely is it that democracies will live up to those expectations? In The State of Democratic Theory, Ian Shapiro offers a critical assessment of contemporary answers to these questions, lays out his distinctive alternative, and explores its implications for policy and political action. Some accounts of democracy's purposes focus on aggregating preferences; others deal with collective deliberation in search of the common good.